Web-based Information Systems in Veterinary Industry - M Iffan; I Firmansyah (International Journal of Education, Information Technology, and Others, 2020)
The purpose of this study is to provide convenience for farmers to market local-breed chickens and facilitate consumers in purchasing it so that consumers do not need to go to the farm. Besides, this study also aims to identify whether the design of a web-based local-breed chickens sales information system can significantly affect the number of sales. In this study, we used a descriptive method, namely by conducting direct interviews with local-breed chickens’ breeder to describe its sales system. The results of this study indicate that the design of sales information systems can provide a significant increase in sales of local-breed chickens. In conclusion, the design of a sales information system for local-breed chickens can help farmers in marketing and selling local-breed chickens at reasonable prices so that farmers get more profits.